What's the problem with "screen time"? A content analysis of dominant voices and worries in three years of national print media. (February 2023) - Størup, Jan Ole; Lieberoth, Andreas
This study examined the various ways in which Danish news media represented digital media as a problem over a period of three years. We present data from a content analysis of 263 newspaper articles and chi-squared analyses identifying associations between worries, voices, culprits, and those responsible for solving problems. We find professionals significantly responsible for framing problems with screen time in terms of mental health issues and addiction, while the broader discourse is one of, for example, time theft, video game addiction, and issues in schools. Technologies are often diffused using "screens" to describe a broad palette of devices/applications, are represented as responsible for distractions while the technology industry is held culpable for effects on social relations and addictive behaviors. We discuss how patterns in media coverage and expert use affects public understandings, and the overall findings that while technologies are represented as responsible for particular problems, the "screen" discourse is a space in which arguments shift between technologies, problems, and authorities.